Analysis of Factors Affecting Poverty Level In Java Island - Varenia Deby Alsya; Nunuk Triwahyuningtyas; Sri Murtatik (Ridwan Institute, 2021)
Java Island is an area that has the highest poverty level in Indonesia for every year. Java Island is a centralization area of economic development, but there is also a poverty problem centered on Java Island. Factors that can affect poverty include total population, income per capita and labor force participation rate. The research was conducted to find out how the influence of total population, income per capita and labor force participation rate on poverty levels in Java Island. The data used in this study are 6 provinces in Java for the period 2013 – 2019, so the panel data regression model is the method used in this study, with the selected model being is Fixed Effect Model (FEM). The results of this study represent that the total population does not effect on poverty levels in Java Island, income per capita has effects on poverty levels in Java Island and the labor force participation rate has effects on poverty levels in Java Island.